2020
DOI: 10.3390/ijerph17010311
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Survey of Residents Living Near a Solid Waste Open Dumpsite in Sabak, Kelantan, Malaysia

Abstract: The management of waste materials is a serious problem worldwide, especially in urbanizing countries like Malaysia. This study was conducted to compare the prevalence of health symptoms and diseases diagnosed among residents exposed to the solid waste open dumpsite in the suburb of Sabak with the non-exposed community. Research related to exposure to solid waste dumping with complete health problems has never been combined in one study. A comparative cross-sectional study was conducted. The exposed group inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…Prior studies have also established a connection between hazards and proximity to Landfill (Thada 2012;Sankoh, Yanm, and Tran 2013;Njoku et al 2018, Njoku, Edokpayi, andOdiyo 2019;Srangsriwong, Olapiriyakul, and Yanradee 2019;Norsa'adah et al 2020). Njoku et al (2018) and Njoku, Edokpayi, and Odiyo (2019) observed that people neighboring landfill expressed dismay at the adverse pollutant fire emanating from the site.…”
Section: Landfill Their Hazards and This Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Prior studies have also established a connection between hazards and proximity to Landfill (Thada 2012;Sankoh, Yanm, and Tran 2013;Njoku et al 2018, Njoku, Edokpayi, andOdiyo 2019;Srangsriwong, Olapiriyakul, and Yanradee 2019;Norsa'adah et al 2020). Njoku et al (2018) and Njoku, Edokpayi, and Odiyo (2019) observed that people neighboring landfill expressed dismay at the adverse pollutant fire emanating from the site.…”
Section: Landfill Their Hazards and This Researchmentioning
confidence: 96%
“…Although, Rovira et al (2015) andNorsa'adah et al (2020) asserted that hazards were prevalent in areas neighboring landfills, the spatial extent of its impact remains unknown and unavailable in the Nigerian literature. There is also not much research on the temporal pattern of these hazards to date.…”
Section: Landfill Their Hazards and This Researchmentioning
confidence: 99%
“…This food waste ended up disposed at landfill, and honestly, the space for these solid wastes was running out. Malaysia had more than 230 landfills and the majority were crude dumping grounds [7][8]. However, the amount of land available will become scarce as more and more open dumping practices occur in most of the landfill in Malaysia.…”
Section: Ffv Wastesmentioning
confidence: 99%
“…Open dumping is another major unscientific practice of waste disposal in many developing countries (Norsa'adah et al, 2020;Singh et al, 2020). In the places where MSW collection systems are not available, people prefer to dump their waste at an unallotted location by the roadsides-usually in streets or in open dumpsites and water streams (Kumar et al, 2017;Mushtaq et al, 2020).…”
Section: Open Dumping Of Wastementioning
confidence: 99%